Answer:
9
Step-by-step explanation:
8.5*9(h)=76.5
76.5+15=91.5
Express each ratio as a fraction in lowest terms.
1) 77 to 490
2) 35 to 135
3) 65:1001
The area of the triangle is given by the functions area of triangle A:x2 + x area of triangle B: x2 - 3x which functions represents the sum of the areas of the two triangles? 1. 4x 2.-4x 3.x2-4x 4.2x2-2x
Answer:
4. 2x^2 - 2x.
Step-by-step explanation:
Adding the 2 functions:
Area of the 2 triangles = x^2 + x + x^2 - 3x
= .2x^2 - 2x
Answer:
OPTION 4
Step-by-step explanation:
Let be f(x) the function that represents the area of Triangle A:
[tex]f(x)=x^2 + x[/tex]
Let be g(x) the function that represents the area of Triangle B:
[tex]g(x)=x^2 - 3x[/tex]
Then, you need to add the area of Triangle A and the area of Triangle B in order to find the sum of the areas (Let be h(x) the function that represents the sum of the the areas of triangles A and B):
Therefore, this is:
[tex]h(x)=(x^2 + x)+(x^2 - 3x)=x^2 + x+x^2 - 3x=2x^2-2x[/tex]
You can notice that this matches with the option 4.
What is the solution to the equation below?
log 20х3 - 2logx = 4
x=25
x=50
x=250
x=500
Answer:
x = 500.
Step-by-step explanation:
log20x^3 - 2logx = 4
By the laws of logs:
log20x^3 - logx^2 = 4
log(20x^3 / x^2) = 4
20x^3 / x^2 = 10^4
20x = 10,000
x = 10,000 / 20
x = 500.
The solution of the given logarithmic equation is x = 500.
What is a logarithmic equation?Any equation in the variable x that contains a logarithm is called a logarithmic equation.
Given logarithmic equation
[tex]log20x^{3} -2logx=4[/tex]
Using [tex]mloga=loga^{m}[/tex]
[tex]log20x^{3} -logx^{2}=4[/tex]
Using [tex]loga-logb=log(\frac{a}{b})[/tex]
[tex]\frac{log20x^{3} }{x^{2} }=4[/tex]
[tex]log20x=4[/tex]
[tex]20x=10^{4}[/tex]
[tex]x=\frac{10000}{20}[/tex]
[tex]x=500[/tex]
The solution of the given logarithmic equation is x = 500.
Find out more information about logarithmic equation here
https://brainly.com/question/14411365
#SPJ2
simplify. rewrite the expression in the form 9^n:
9^-3/9^12
Answer:
9 ^ (-15)
Step-by-step explanation:
9^-3/9^12
We know that a^b/ a^c = a^(b-c)
9^-3/9^12 = 9 ^(-3-12)
=9^(-15)
The expression [tex]\frac{9^{-3}}{9^{12} }[/tex] written in the form [tex]9^{n}[/tex] is [tex]9^{-15}[/tex]
From the question,
we are to rewrite the given expression (9^-3/9^12) in the form 9^n
First, write the expressions properly.
The given expression is
[tex]\frac{9^{-3}}{9^{12} }[/tex]
To rewrite the given expression in the form [tex]9^{n}[/tex], we will use the division law of indices
From the division law of indices, we have that
[tex]x^{y} \div x^{z}= x^{y-z}[/tex]
Then, the given expression becomes
[tex]\frac{9^{-3}}{9^{12} } = 9^{-3} \div 9^{12}[/tex]
[tex]= 9^{-3-12}[/tex]
[tex]=9^{-15}[/tex]
Hence, the expression [tex]\frac{9^{-3}}{9^{12} }[/tex] written in the form [tex]9^{n}[/tex] is [tex]9^{-15}[/tex]
Learn more here: https://brainly.com/question/18205419
The table shows the number of degrees the temperature increased or decreased over four days. On which day did the temperature change have the greatest magnitude?
A 26 foot rope is used to brace a tent pole at the county fair. the rope is anchored 10 feet from the box of the pole. How tall is the pole? (answers above^^)
Using the Pythagorean theorem a^2 + b^2 = c^2 where a and b are the side and bottom of the triangle and c is the hypotenuse ( length of rope).
Let the tent pole = a
Lhe distance from the pole be b = 10 ft.
The length of rope would vce c = 26 ft.
Now you have:
a^2 + 10^2 = 26^2
Simplify:
a^2 + 100 = 676
Now subtract 100 from each side:
a^2 = 576
To get a, take the square root of both sides:
a = √576
a = 24
The tent pole is B. 24 ft
how much must you deposit in an account that pays 6.25% interest compounded annually to have a balance of $700 after 2 years
Answer:
[tex]\$620.07[/tex]
Step-by-step explanation:
we know that
The compound interest formula is equal to
[tex]A=P(1+\frac{r}{n})^{nt}[/tex]
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest in decimal
t is Number of Time Periods
n is the number of times interest is compounded per year
in this problem we have
[tex]t=2\ years\\A=\$700\\ r=0.0625\\n=1[/tex]
substitute in the formula above and solve for P
[tex]700=P*(1+\frac{0.0625}{1})^{2}[/tex]
[tex]700=P*(1.0625)^{2}[/tex]
[tex]P=700/(1.0625)^{2}[/tex]
[tex]P=\$620.07[/tex]
A triangle has two sides of lengths 10 and 14. What value could the third side be?
Answer:B, C, D, E.
Step-by-step explanation:
The third side of a triangle with two sides measuring 10 and 14 units must be greater than 4 and less than 24 units. This is determined using the Triangle Inequality Theorem.
The possible values for the third side of a triangle with sides of lengths 10 and 14 can be found using the Triangle Inequality Theorem.
Add the two given side lengths: 10 + 14 = 24.
To find the range of possible values for the third side, subtract the two given side lengths from the total: 24 - 10 = 14, and 24 - 14 = 10.
Therefore, the third side of the triangle must have a length greater than 4 but less than 24.
Add the two expressions.
−2.4n−3 and −7.8n+2
Enter your answer in the box.
Answer:
-10.2n - 1
Step-by-step explanation:
−2.4n − 3 + (−7.8n + 2) =
= -2.4n - 7.8n - 3 + 2
= -10.2n - 1
Answer:
-10.2n -1
Step-by-step explanation:
−2.4n−3 + −7.8n+2
Combine like terms
−2.4n −7.8n -3+2
-10.2n -1
Find the mean of the data set that consists of 3, 11, 4, 3, 10, 6, 4, 5.
A. 3 and 4
B. 4.5
C. 5.75
D. 5.25
Answer:
5.75
Step-by-step explanation:
[tex]3 + 11 + 4 + 3 + 10 + 6 + 4 + 5 = 46 \\ 46 \div 8 = 5.75[/tex]
The total amount of numbers are : 8
To find the mean, we calculate the sum of all values and divide that sum by the amount of numbers there are.
PLEASE DO MARK ME AS BRAINLIEST IF MY ANSWER IS HELPFUL :)
Which are correct representations of the inequality –3(2x – 5) < 5(2 – x)? Check all that apply.
x < 5
–6x – 5 < 10 – x
–6x + 15 < 10 – 5x
Answer:
[tex]-6x+15< 10-5x[/tex]
Step-by-step explanation:
we have
[tex]-3(2x-5) < 5(2-x)[/tex]
solve for x
eliminate the parenthesis (apply the distributive property)
[tex]-3*2x+3*5 < 5*2-5*x[/tex]
[tex]-6x+15< 10-5x[/tex] ---> correct representation of the inequality
Adds (5x-15) both sides
[tex]-6x+15+5x-15< 10-5x+5x-15[/tex]
[tex]-x< -5[/tex]
Multiply by -1 both sides
[tex]x>5[/tex]
Solve x - (-9) = -14. -23 23 -5 5
Answer:
-23 = x
Step-by-step explanation:
-(-9) = 9
The thing with double negatives is that they form a plus sign, so that is really a POSITIVE nine. Therefore you do the inverse to find x: -14 - 9 = -23.
I am joyous to assist you anytime.
Answer:
[tex]\Huge \boxed{X=-23}[/tex]
Step-by-step explanation:
[tex]\displaystyle x+9=-14[/tex]
[tex]\Large\textnormal{First, subtract by 9 from both sides of equation.}[/tex]
[tex]\displaystyle x+9-9=-14-9[/tex]
[tex]\Large\textnormal{Simplify, to find the answer.}[/tex]
[tex]\displaystyle -14-9=-23[/tex]
[tex]\Large\textnormal{x=-23, which is our answer.}[/tex]
[tex]4c - d - c - 3d[/tex]
[tex]\tt 4c-d-c-3d=3c-4d[/tex]
Answer:
3c -4d
Step-by-step explanation:
4c -d -c -3d
Combine like terms
4c -c -d -3d
3c -4d
A: What are the solutions to the quadratic equation?
B: which statements accurately interpret the solution?
Answer:
A. x = -1 or x = 3B. firstStep-by-step explanation:
[tex]x^2-2x-3=0\\\\x^2+x-3x-3=0\\\\x(x+1)-3(x+1)=0\\\\(x+1)(x-3)=0\iff x+1=0\ \vee\ x-3=0\\\\x+1=0\qquad\text{subtract 1 from both sides}\\x=-1\\\\x-3=0\qquad\text{add 3 to both sides}\\x=3[/tex]
Do you prefer to express solutions to inequalities using interval notation or as an inequality? Do you think it is important to know both formats? How could each be used?
Answer:
I prefer to express solutions to inequalities using interval notation. Both formats are are important but I think interval notation is easier to understand and represents better the solutions.
For example, if you have the following inequation:
x-2> 1
x>3
Therefore, the solution could be written either x>3 OR (3, +inf). But what happens if the solution to the system of equation is x>3 or x<-3? The solution can be easily written as: (-inf, -3) U (3, inf) instead of 'x>3 or x<-3' which can be confusing.
To express solutions to inequalities using interval notation.
I prefer to express solutions to inequalities using interval notation. Both formats are important but I think interval notation is easier to understand and represents better the solutions.
For example, if you have the following inequation:
x-2> 1
x>3
Therefore, the solution could be written either x>3 OR (3, +inf). But what happens if the solution to the system of equation is x>3 or x<-3? The solution can be easily written as: (-inf, -3) U (3, inf) instead of 'x>3 or x<-3' which can be confusing.
Hence, To express solutions to inequalities using interval notation.
Learn more about interval notations here https://brainly.com/question/18586505
#SPJ2
Students observing a caterpillar crawl on a tree noticed that the caterpillar crawled upwards 38 of an inch every minute. The caterpillar was already 4.5 feet off the ground when the students began observing.
Which function represents the total number of inches the caterpillar crawls after x minutes?
f(x) = 4.5x + 3/8
f(x) = 54x + 3/8
f(x( = 3/8x + 54
f(x) = 3/8x + 4.5
Answer:
f(x) = 4.5x + 3/8
Answer: Third Option
[tex]f(x) = \frac{3}{8}x + 54[/tex]
Step-by-step explanation:
We want to propose an equation that models the distance traveled by the caterpillar as a function of time, we have a constant initial quantity of 4.5 feet and then we know that every minute the caterpillar advances 3/8 of an inch
Then the distance that the caterpillar to advanced after x minutes is:
[tex]f(x) = \frac{3}{8}x[/tex]
Then we know that initially the caterpillar was at a distance of 4.5 feet or 54 inch
Then the equation for the distance in inch is:
[tex]f(x) = \frac{3}{8}x + 54[/tex]
If triangle DEC congruent to triangle BEC, which is true by CPCTC?
Answer:
The correct answer is the second one
Step-by-step explanation:
Line BE and ED are congruent because they are the same length and E is the mid line.
Answer:
second option is correct
Step-by-step explanation:
By the given
ΔDEC≅ΔBEC
which means triangle DEC is congruent to triangle BEC
then by CPCTC (corresponding parts of congruent triangle are congruent)
there every side and angle of DEC will be equal to BEC
⇒BE= DE (by CPCTC)
hence second option is correct
Question number 8 please please fast
Answer:
[tex]a_n=-\frac{1}{n}[/tex]
[tex]a_6=-\frac{1}{6}[/tex] is our sixth term.
[tex]a_7=-\frac{1}{7}[/tex] is our seventh term.
[tex]a_8=-\frac{1}{8}[/tex] is our eighth term.
Step-by-step explanation:
So every number in this sequence is -.
If you write 1 as 1/1, then you should see the numerator is constant one while the denominator is going up by 1 each time.
So the patter is
[tex]a_n=-\frac{1}{n}[/tex]
Test if you like:
n=1 gives us [tex]a_1=-\frac{1}{1}=-1[/tex] which is our first term.
n=2 gives us [tex]a_2=-\frac{1}{2}[/tex] which is our second term.
n=3 gives us [tex]a_3=-\frac{1}{3}[/tex] which is our third term.
n=4 gives us [tex]a_4=-\frac{1}{4}[/tex] which is our fourth term.
n=5 gives us [tex]a_5=-\frac{1}{5}[/tex] which is our fifth term.
Now we are going to use [tex]a_n=-\frac{1}{n}[/tex]
to write our next three terms:
n=6 gives us [tex]a_6=-\frac{1}{6}[/tex] which is our sixth term.
n=7 gives us [tex]a_7=-\frac{1}{7}[/tex] which is our seventh term.
n=8 gives us [tex]a_8=-\frac{1}{8}[/tex] which is our eighth term.
Find the num
The sum of a number and its reciprocal 10/3. find the number 5
Answer:
x=3 or x= 1/3
Step-by-step explanation:
Let the number = x
The reciprocal of the number = 1/x
According to the given statement:
x+1/x=10/3
x²+1/x=10/3
3(x²+1)=10x
3x²+3=10x
Move 10x to the L.H.S
3x²-10x+3=0
Break the middle term:
3x²-9x-x+3=0
3x(x-3)-1(x-3)=0
(x-3)(3x-1)=0
x-3=0 , 3x-1=0
x=0+3 , 3x=0+1
x=3 , 3x=1
x=3 ,x = 1/3
So x=3 or x= 1/3 ....
Find an equation for the inverse of the function. f(x)=2x-3x/4
Answer:
f⁻¹(x) = (4x)/5
Step-by-step explanation:
f(x) = 2x - 3x/4.
Assume y=f(x). Therefore:
y = 2x - 3x/4.
Make x the subject in the above equation.
y = (2x(4) - 3x)/4.
y = 5x/4.
4y = 5x.
(4y)/5 = x.
x = (4y)/5.
Therefore:
f(y) = (4y)/5.
Replace y with x.
f⁻¹(x) = (4x)/5.
Therefore, the inverse of f(x) = 2x - 3x/4 is f⁻¹(x) = (4x)/5!!!
Consider the polynomial p(x)=x^3-9x^2+18x-25, which can be rewritten as p(x)=(x-7)(x^2-2x+4)+3. The number blank is the remainder when p(x) is divided by x-7, and so x-7 blank a factor of p(x). Fill in the two blanks with is, 3, 7,is not, or 0!!!!
PLEASE HELP. WILL MARK BRAINLIEST!!
Answer:
[tex]\boxed{\text{3; is not}}[/tex]
Step-by-step explanation:
[tex]\begin{array}{rcl}p(x) & = & (x - 7)(x^{2} - 2x + 4) + 3\\\\\dfrac{p(x)}{x - 7} & = &x^{2} - 2x + 4 + \dfrac{3 }{x-7 }\\\\\end{array}\\\\\text{The number }\boxed{\mathbf{3}}\text{ is the remainder when $p(x)$ is divided by $(x - 7)$,}\\\\\text{so $(x - 7)$ }\boxed{\textbf{is not}} \text{ a factor of $p(x)$.}[/tex]
Write the expression in complete factored form. 2n^2(q+8)-(q+8)=
(q+8)(2n^2-1)
I think this is the correct form.
Which is the graph of linear inequality 2 y > x – 2?
Answer:
Third graph
Step-by-step explanation:
We are determine whether which of the given graphs is that of the linear inequality [tex]2y>x-2[/tex].
We know that, on the graph the greater than sign ([tex]>[/tex]) represents the shaded part above the line and less than sign ([tex]<[/tex]) represents the shaded region below the line.
While the signs [tex]\leq[/tex] or [tex]\geq[/tex] is denoted by a solid line on the graph.
Therefore, the third graph represents the given inequality.
Answer:
The graph in the attached figure
Step-by-step explanation:
we have
2y > x-2
The solution of this inequality is the shaded area above the dotted line 2y=x-2
The graph in the attached figure
6 plus 9 rquals to 10 plus WHAT NUMBER????
Answer: 5.
Step-by-step explanation:
6+9 = 15
10 + x = 15
-10 -10
x = 5
Answer:
x=5
Step-by-step explanation:
6+9=10+x
15=10+x
x=15-10
x=5
Which is the best estimate of the circumference of this circle?
Answer:
12 is the best estimate
Answer:
option A.
Step-by-step explanation:
We have to find the circumference of the given circle with radius 2 units.
Since formula to calculate circumference of a circle is = 2πr
Where r = radius of the circle.
Circumference = 2 × (3.14) × (2)
= 4 × 3.14
= 12.56
So approximate value will be option A.
Help please the graphs below Have the same shape. What is the equation of the blue graph
Answer:
D. G(x) = (x+2)^2
Step-by-step explanation:
We can easily solve this problem by graphing each case with a graphing calculator or any plotting tool.
The equations are
A. G(x) = (x-2)^2
B. G(x) = (x)^2 + 2
C. G(x) = (x)^2 -2
D. G(x) = (x+2)^2
Se attached image.
The correct option is
D. G(x) = (x+2)^2
Answer:
C. G(x)=x²-2
Step-by-step explanation:
The midpoint of the graph has been displaced from x=0 to x=-2. this is a negative displacement.
Therefore the new equation G(x)=x²-2
This is because there is no tilt in the graph so it is a replica of the red graph.
If f(x) = x^2 + 1 and g(x) = x - 4, which value is equivalent to (fºg)(10)?
Answer:
37
Step-by-step explanation:
Substitute x = 10 into g(x), then substitute the result into f(x)
g(10) = 10 - 4 = 6, then
f(6) = 6² + 1 = 36 + 1 = 37
For Sophia's graduation party, several tables of the same width will be arranged end to end to form a serving table with a
total area of 75 ft. The total length of the tables will be two more than three times the width. Find the length and width of
the serving table so that Sophia can purchase the correct table cloth. Round your answers to the nearest tenth.
Area: 75 ft
Bw + 2
Answer:
Width=4.7 ft
Length=16.1 ft
Step-by-step explanation:
Let the width of the table to be x ft
Then the length should be two more than three times the width= 2+3x ft
The area of the serving table should be 75 ft²
But you know the area of this table is calculated by multiplying the length by the width of the table
Hence, Area= length× width
Length=x ft and width =2+3x ft
75ft²= (x ft) × (2+3x ft)
[tex]75=x*(2+3x)\\\\75=2x+3x^2\\\\3x^2+2x-75=0[/tex]
Apply the quadratic formula to solve this quadratic equation
The formula is ;
x= (-b ±√b²-4ac)÷2ac
where a=3, b=2 and c=-75
x= (-2 ± √2²-4×3×-75)÷(2×3)
x=(-2±√4+900)÷6
x=(-2±√904)÷6
x=(-2±30.1)÷6
x=(-2+30.1)÷6=4.683⇒4.7(nearest tenth)
or
x=(-2-30.1)÷6= -32.1÷6=-5.35⇒ -5.4
Taking the positive value
x=width =4.7 ft
2+3x= length= 2+3(4.7)=16.1 ft
the equation of a line in the point slope form is show below.
Answer:
A 3
Step-by-step explanation:
y-9 = 3(x-9)
This is in point slope form
y-y1 = m(x-x1)
where (x1,y1) is the point and m is the slope
A point on the line is (9,9) and the slope is 3
The fuel consumption in miles per gallon for a car varies inversely with its weight. Suppose a car that weighs 2800 pounds get 33 miles per gallon on the highway. Write the equation that relates y, the fuel consumption in miles per gallon, to the car's weight, w pounds.
Answer:
y=0.01179/w
Step-by-step explanation:
First understand that the fuel consumption in miles per gallon is inversely proportional to the weight of a car.
If y is the fuel consumption in miles per gallon and w is weight of car in pounds . you can write the first statement as;
y∝1/w
Introduce a constant value for proportionality, k
y=k/w....................make k subject of the formula by multiplying both sides by 1/w
k=y/w
Given in the question that ;
w=2800
y=33
k=?
To find k , apply the formula that you derived above
k=y/w
k=33/2800 =0.011785⇒0.01178(4 significant figures)
Rewrite the formula as
y=k/w ⇒ y=0.01179/w
The equation that relates y and w is;
y=0.01179/w
The fuel consumption in miles per gallon for a car varies inversely with its weight and can be represented mathematically by the inverse proportionality relationship y = k/w. Substituting the given values gives us the constant k = 92400, so the final equation is y = 92400/w.
Explanation:This problem can be defined mathematically by an inverse proportionality relationship, expressed as y = k/w, where k is a constant, y is the fuel consumption in miles per gallon, and w is the weight of the car in pounds.
To find the value of k, we can substitute the given values into the equation. This gives us 33 = k/2800, which simplifies to k = 33 * 2800, or k = 92400.
So, the equation that relates the mileage per gallon, y, to the weight of the car, w, is y = 92400/w. This means the fuel efficiency of a car decreases as its weight increases, thus heavier cars tend to have lower miles per gallon.
Learn more about Inverse Proportionality here:https://brainly.com/question/14437120
#SPJ3